The Anatomy of Job Satisfaction and the Role of Contingent Employment Contracts - Marloes de Graaf-Zijl (Tinbergen Institute, 2005)
In this paper I analyse job satisfaction using fixed effect analysis and a multiple equation model. Overall job satisfaction is analysed as an aggregate of satisfaction with several job aspects. I find that overall job satisfaction is mainly determined by satisfaction with job content. All aspect satisfactions are subsequently explained from observed characteristics, with special focus on contingent employment contracts. Satisfaction with job security is the aspect satisfaction with the strongest relation to type of contract. Since this is also the aspect that receives least weight in overall job satisfaction this has little impact on workers' total happiness. More influential is the low satisfaction with job content due to agency work. Overall, temporary agency work leads to the lowest job satisfaction. On-call work and fixed-term work arrangements do not differ from regular work in overall job satisfaction they provide, even though they do lead to highe! r or lower satisfaction with some aspects of the job.
Keywords: J28; J40; C23; 330; temporary employment; job satisfaction